2014
DOI: 10.1080/15287394.2014.955906
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Cedrol, β-Cedrene, and Thujopsene on Cytochrome P450 Enzyme Activities in Human Liver Microsomes

Abstract: Cedrol, β-cedrene, and thujopsene are bioactive sesquiterpenes found in cedar essential oil and exert antiseptic, anti-inflammatory, antispasmodic, tonic, astringent, diuretic, sedative, insecticidal, and antifungal activities. These compounds are used globally in traditional medicine and cosmetics. The aim of this study was to investigate the inhibitory effects of cedrol, β-cedrene, and thujopsene on the activities of eight major human cytochrome P-450 (CYP) enzymes using human liver microsomes to assess pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…It is important to note, however, that the inhibition of CYP2B6 and CYP3A4 activity in vitro does not necessarily translate into drug–drug interactions in clinical situations. To predict any possible drug–drug interaction potential of cedrol, β‐cedrene, and thujopsene, pharmacokinetic studies of these components and in vivo studies are required to determine the clinical relevance of CYP2B6 and CYP3A4 inhibition …”
Section: Inhalation Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note, however, that the inhibition of CYP2B6 and CYP3A4 activity in vitro does not necessarily translate into drug–drug interactions in clinical situations. To predict any possible drug–drug interaction potential of cedrol, β‐cedrene, and thujopsene, pharmacokinetic studies of these components and in vivo studies are required to determine the clinical relevance of CYP2B6 and CYP3A4 inhibition …”
Section: Inhalation Productsmentioning
confidence: 99%
“…To predict any possible drug-drug interaction potential of cedrol, β-cedrene, and thujopsene, pharmacokinetic studies of these components and in vivo studies are required to determine the clinical relevance of CYP2B6 and CYP3A4 inhibition. 56…”
Section: Cedrol β-Cedrene and Thujopsenementioning
confidence: 99%
“…As an example, α-pinene and cedrol-rich oil could be effectively used as a local antiseptic. [32] Moreover, J. excelsa oils could be used as naturally derived preservatives due to the limonene-rich content. Namely, limonene is capable of reducing microbial contamination and preventing food spoilage in a wide range of food, but without adversely altering the taste or function.…”
Section: Chemical Profile Of J Excelsa Essential Oilsmentioning
confidence: 99%
“…For instance, caryophyllene, one of the bicyclic sesquiterpenes has potential antioxidant, anti-inflammatory, and antimicrobial activities (Sharma et al, 2016). Another compounds such as cedrol (a sesquiterpene alcohol), cedrene, and thujopsene possess inhibitory effects against cytochrome P450 (CYP) enzyme (CYP2B6 and CYP3A4) in human liver microsomes in vitro as well as anti-inflammatory, antifungal, insecticidal, diuretic, antispasmodic, astringent, sedative and antiseptic properties (Jeong et al, 2014). All phytochemicals detected in the ethyl acetate extracts of M. micrantha in present study was reported for the first time, except α-Longipinene, β-Himachalene, β-Cubebene, and α-Zingiberene, which were also reported in the previous study of the essential oil composition of M. micrantha from China (Zhang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%